Mechanical stretching induces chromatin remodeling: understanding the epigenetic landscape involved in fibrosis - Lambert, Addison, author; Ghosh, Soham, advisor; Prasad, Ashok, committee member; Zhao, Jianguo, committee member (Colorado State University. Libraries, 2025)
Fibrosis is a hallmark of many degenerative diseases across multiple organs and tissues and is responsible for around 45% of death in the developed world. It is a complex process driven by many factors with mechanical stress emerging as a critical player in the progression of fibrosis. However, the precise mechanism of fibrosis by mechanical forces is unknown. The goal of this thesis is to find the epigenetic basis of how fibrosis is induced inside cells using a mechanical stretching model applied to fibroblasts, a common cell type in many organs and tissues and a key player in fibrotic diseases. Epigenetics is the investigation of how genes are expressed by chemical factors working at the chromatin architecture level. Previous studies showed that mechanical forces can drive the epigenetic process, but such possibilities are less understood in the progression of fibrotic disease. In this study a mechanical stretching platform was created and validated to investigate the mechanical stretching on the nucleus and chromatin of fibroblasts. Stretching increased the collagen production as discovered by immunofluorescence, and chromatin compacted as a result of stretching as found from an increased H3K9Me3 level in the nucleus. To investigate the dynamics of chromatin compaction as measured by area changes, time lapse microscopy was performed on fibroblast nuclei. It was further found that drugs targeting the histone modification can affect the chromatin compaction suggesting a mechanics driven, histone assisted process of chromatin remodeling. Then it was shown, using high-resolution time-lapse microscopy on individual nuclei that under stretching, that chromatin remodels dynamically. This data suggests that under mechanical stretching fibroblast nuclei undergo dynamic changes which might have implications in the longer-term genomic stability and gene expression levels. This thesis creates the framework to investigate the mechanism of mechanics inducing fibrotic changes in cells that can help in better understanding the fibrosis process.
Keywords: epigenetics; mechanical strain; chromatin remodelling; mechanotransduction; fibrosis